The invisible coup : how American elites and foreign powers use immigration as a weapon - Schweizer, Peter, 1964- (Harper, an imprint of HarperCollinsPublishers, 2026)
"Our debates about immigration revolve around what happens with immigrants once they arrive. [The author believes that] we need to start talking about who is sending them and why. For decades, establishment elites sold us the story of immigration as a compassionate renewal of the American Dream within a harmonious melting pot. But beneath that narrative lies a different reality: mass migration has morphed into the most powerful political weapon ever aimed at the UnitedStates--one engineered by elites at home and aided by adversaries abroad"--